On the Perov Integro-Summable Inequality for Functions of Two Variables - Massalitina, E. V. (Ukrains’kyi Matematychnyi Zhurnal, 2004)
We present a generalization of the Perov integral inequality for functions of two variables in the case of discontinuous functions.